PERAN MASJID SEBAGAI BASIS PERADABAN ISLAM - Ahlan Ahlan (Universitas Islam Malang, 2022)
The mosque is the first building built by the Prophet Muhammad, after making the hijra to Medina. The mosque in the early days of Islam had a multifunction which was not limited to its function only as a place for the implementation of the Mahdhah worship but also as a place for the Gairu Mahdhah worship. Thus, it can be seen that in terms of its historical roots, the mosque has functioned in such a way, not only as a place of special worship, but has also functioned in worldly affairs, which are oriented towards fostering human resources. Today, if we observe, the use of the mosque is slightly different from what the Prophet had exemplified in the early days of Islam. In the Messenger of Allah, the mosque functioned as a center for the development of civilization, not only for worship, because every problem and idea to improve the people was resolved in the mosque. So it is only natural that the mosque is returned to its original function which is the central point of the presence of a great civilization in Islamic history. So that activities in the mosque are not only a place to carry out the main worship but must also be the birthplace of knowledge, cultural centers, social activities, developing the economy, running politics, as well as a place to revive the arts.